Doeltreffende keuringsonderhoude: Die taak van lynbestuur - David Tromp (South African Journal of Business Management, 1982)
Effective selection interviews: The task of line management The selection interview still remains one of the most important and most commonly used selection techniques. During their formal training personnel officials are normally taught how to conduct selection interviews in a professional and effective way. However, the final responsibility for the selection decision still rests with the line manager but he often lacks the skills necessary to conduct a good selection interview. The result of this is that a highly intuitive and risky decision is taken. In this article the most important errors which interviewers make, are discussed. These errors relate in the first instance to the way in which selection interviews are conducted and the resulting shortcomings in communication which have a negative effect on the availability of the information required for decision-making. Secondly, errors are often made in respect of the interpretation and evaluation of this information. A procedure for eliminating these errors is proposed of which the main components are a semi-structured approach and the use of an interview appraisal form based on the prior identification of the required behavioural dimensions.
Keywords: 650